The Digital Age: A Feminist Future for the Queer African Woman. (July 2015) - McLean, Nyx; Mugo, Tiffany Kagure
Abstract How can digital spaces make possible a feminist future for the queer African woman? Writing as the editors of a South African queer online space, HOLAA!, this article aims to draw attention to and discuss queer digital communities and how they afford the queer African woman the space to express her lived experiences. The article further examines how digital spaces create these possibilities for public and political expression. Lastly, the authors present what they consider to be a feminist future for the queer African woman, and that it is within this future that the rights of queer women can be protected nationally and internationally as the conversations that fight erasure, exclusion and the denial of rights occur.